Research on the Global Communication of Traditional Chinese Medicine from the Perspective of Cognitive Linguistics - Zheng, Jie; Luo, Ruifeng (Journal of Ecohumanism, 2024)
Chinese medicine is one of the important traditional cultures of the Chinese nation, a typical representative of the unique wisdom of the nation, and an influential worldwide cultural label of the country. In this paper, the theory of Cognitive Linguistics is used to enhance the depth of cultural communication of traditional Chinese medicine, to make up for the shortcomings of single language, mode and means in the communication research of traditional Chinese medicine at home and abroad, and to provide innovative research routes for the communication of traditional Chinese medicine at home and abroad, such as cognitive neuroscience and artificial intelligence big data, which conform to the development of the times. From a practical point of view, it will provide solutions for the internal and external communication of Chinese medicine more empirically and scientifically, and more effectively promote the Chinese medicine culture to take root in the local area and go global. Especially, it will gain the recognition of the younger generation who are good at obtaining information from new media through high-quality audio-visual translation products of Chinese medicine, so as to build a human health community with Chinese medicine as an important part.